A Dataset on Linguistic Connectivity Across and Within Countries - Tamara Gurevich; Peter R. Herman; Farid Toubal; Yoto V. Yotov (Scientific Data)
Abstract We construct a new global dataset on common language. The data cover 242 countries and territories and are based on information about the speakers of 6,675 languages. Using data from Ethnologue, we provide 11 bilateral measures reflecting different dimensions of linguistic connections within and between countries, including common official languages, common native and acquired languages, and linguistic proximity across different languages. A key novelty of the dataset is that it includes consistently defined information on linguistic relationships not only between different countries but within the administrative borders of countries as well.